New differential medium for the isolation of Corynebacterium vaginale. - Mickelsen, P A (1977)
A new differential medium for isolation of Corynebacterium vaginale is described. This opaque medium containing 1% corn starch allows detection of C. vaginale by the zones of clearing developing around the colonies.